Predictive Analysis of Variables Related with the Adoption of Quality Control Practices by the Shrimp Freezing Plants - M.K., Kandoran; S., Balasubramaniam; Thomas, Mary; R., Thiagarajan; A.K.K., Nair (Fishery Technology, 2025)
This paper analyses the differential characteristics and adoption of quality control practices among the shrimp freezing plants in lndia. The mean adoption quotient scores calculated for the three categories of freezing units viz., Quality Control and Inspection in Approved Units, ln-process Quality Control and combined samples, were found to be quite high (79.20%, 83.99% and 80.92%). ’lhe regression analysis of the combined sample revealed that the four variables viz. the number of years of functioning as shrimp freezing plant, ice production mpacity, number of technical personnel and number of years of experience of the senior technologist were found to have significant influence on the extent of adoption of quality control practices.